0521 Daridorexant (ACT-541468), A Dual Orexin Receptor Antagonist for the Treatment of Insomnia Disorder: Double Blind, Randomized, Phase 3 Studies for Efficacy and Safety in Adult and Elderly Patients. (27th May 2020) - Zammit, G; Seboek Kinter, D; Bassetti, C; Leger, D; Hermann, V; Pain, S; Roth, T
Abstract: Introduction: Daridorexant, a potent and selective orally administered dual orexin receptor antagonist (DORA), has shown dose-dependent efficacy and is well tolerated with minimal residual next-morning effects in two phase 2 studies in adult and elderly subjects with insomnia disorder. Following the favorable phase 2 results, clinical development was pursued with two pivotal phase 3 multi-center, double-blind, randomized, placebo-controlled studies to further assess efficacy and safety in adult and elderly subjects with insomnia disorder. Long-term safety and tolerability are being further evaluated in a double-blind placebo-controlled extension study. Methods: Each of the pivotal studies include ~900 patients (~40% ≥65y), randomized 1:1:1 to one of two daridorexant arms or placebo. The studies differ in dose only (10 or 25 mg [NCT03545191], 25 or 50 mg [NCT03575104]). Both report objective primary outcomes at 1 and 3 months based on PSG (WASO and LSP). Secondary endpoints include self-reported nighttime benefit with Total Sleep Time (sTST), and daytime benefit using the validated Insomnia Daytime Symptoms and Impacts Questionnaire (IDSIQ). The patients undergo screening (7-13 d) and run-in (7-18 d) periods establishing eligibility and baseline, a 3-month double-blind treatment period, followed by a placebo run-out (7 d) to evaluate rebound insomnia and withdrawal effects and a 30-day safety follow-up. Additionally, subjects completing treatment could enroll in the 40-week double-blinded placebo-controlled extension trial [NCT03679884] to assess long-term safety. Results: Enrollment in NCT03575104 (25/50 mg) was successfully completed and involves 76 sites across 10 countries; expected completion March 2020. Recruitment to study NCT03545191 (10/25 mg) is advanced; completion expected June 2020. Conclusion: The comprehensive daridorexant phase 3 program includes 3 dose levels and replication of objective and subjective measurements at 1 and 3 months, while assessing self-reported nighttime benefit, and benefit during the day with a validated PRO instrument, as well as safety in insomnia disorder. Support: Medical writing Randall Watson, (Idorsia). These studies were sponsored by Idorsia Pharmaceuticals Ltd.